2015
DOI: 10.3171/2015.7.focus15245
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of open wounds as a complication of spinal surgery with flaps: a systematic review

Abstract: OBJECT A systematic review of the available evidence on the prophylactic and therapeutic use of flaps for the coverage of complex spinal soft-tissue defects was performed to determine if the use of flaps reduces postoperative complications and improves patient outcomes. METHODS A PubMed database search was performed to identify English-language articles published between 1990 and 2014 that contained the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 35 publications
2
41
1
Order By: Relevance
“…In our hands, soft tissue defects of the posterior trunk or spinal area can be successfully treated using paraspinal perforator flaps with low donor site morbidity. In our retrospective study including 20 patients, we observed a similar complication rate in paraspinal perforator flaps compared to muscle flap coverage (14). From our experience, complete dissection of perforators should be minimized in flap rotation is less than 90˚.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In our hands, soft tissue defects of the posterior trunk or spinal area can be successfully treated using paraspinal perforator flaps with low donor site morbidity. In our retrospective study including 20 patients, we observed a similar complication rate in paraspinal perforator flaps compared to muscle flap coverage (14). From our experience, complete dissection of perforators should be minimized in flap rotation is less than 90˚.…”
Section: Discussionsupporting
confidence: 53%
“…In our series, we exclusively performed delayed defect restoration. Most recent articles propose prophylactic (immediate) wound coverage with well-vascularized tissue in high-risk patients, to decrease the incidence of postoperative wound healing complications after spinal surgery (4,14). In published studies regarding benefits of immediate reconstruction, mostly muscle flaps were used for defect closure (4,18,26).…”
Section: Discussionmentioning
confidence: 99%
“…14 In patients undergoing extensive spinal tumor resection, wound complications can be particularly devastating because of the risk of exposed hardware or neural structures. Subsequent reoperations and washouts potentiate the risk for hardware removal, which can cause long-term deformity and neural injury.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction of complex back defects, especially following spinal surgery, presents a variety of challenges for the reconstructive surgeon, and such cases may be additionally complicated by previous surgeries, planned instrumentation, and altered anatomy. Furthermore, patients undergoing spinal surgery and subsequent reconstruction are subject to a multitude of postoperative complications, including infection, wound‐dehiscence, seroma, hematoma, hardware exposure, and cerebrospinal fluid leak (Chieng et al, ; Rozen et al, ; Saint‐Cyr et al, ). However, it has been shown that adequate coverage of posterior trunk defects with robust muscle flaps both decreased postreconstructive complication rates, and provide strategies for the salvage of infected hardware (Cohen et al, ; Dumanian et al, ; Hultman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction of complex back defects, especially after corrective spine surgery, poses a demanding problem for both the patient and the reconstructive surgeon. Complications such as infection, wound‐dehiscence, seroma, hematoma, and hardware exposure have been reported with rates between 6% and 30% in such patients (Chieng, Hubbard, Salgado, Levi, & Chim, ; Cohen et al, ; Mericli et al, ). Furthermore, particular subunits of the back present even greater reconstructive challenges, specifically the central region between T9 and T12.…”
Section: Introductionmentioning
confidence: 99%